Bearing capacity, small-strain stiffness and air permeability of non-standard compacted soils related to suction. Issue 11 (2nd November 2018) - Andrianatrehina, Soanarivo Rinah; Taibi, Said; Boutonnier, Luc
Abstract : This paper presents an experimental investigation of the hydro-mechanical behaviour of two compacted non-standard soils with respect to the French standards GTR 92 in the framework of embankment construction (a low plasticity silt and a high plasticity marl). The aim is to establish relationships between the mechanical parameters (small-strain stiffness, bearing capacity index I BCR …) and hydraulic parameters (water and air permeabilities, and suction). Results show that, for water content lower than the optimum water content, the small-strain stiffness, I BCR index, air permeability and suction change little with water content, whereas for water content larger than the optimum, there is a sharp drop of all the parameters.